2023
DOI: 10.1186/s10020-023-00735-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin attenuates chronic kidney disease by inhibiting renal tubular epithelial cell ferroptosis via NRF2 activation

Jiayu Song,
Hongri Wang,
Jingyi Sheng
et al.

Abstract: Background Chronic kidney disease (CKD) involves a variety of pathological processes, and ferroptosis plays a vital role in CKD progression. Targeting ferroptosis is a promising strategy for the treatment of CKD. However, inhibitors of ferroptosis have not been used in the clinical treatment of CKD. Vitexin is a natural flavonoid with many biological activities and protective effects against various diseases. However, whether vitexin can prevent the progression of CKD is not known. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It has been reported that the Keap1/Nrf2 pathway participates in regulating several cellular processes, such as fibrosis 46 and autophagy. 44 Under physiological conditions, Nrf2 is produced and degraded, regulated by Keap1 via the pathway of ubiquitination, but under stress conditions, Nrf2 is released from Keap1 and enters the cell nucleus, which transactivates a large number of antioxidants, including HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the Keap1/Nrf2 pathway participates in regulating several cellular processes, such as fibrosis 46 and autophagy. 44 Under physiological conditions, Nrf2 is produced and degraded, regulated by Keap1 via the pathway of ubiquitination, but under stress conditions, Nrf2 is released from Keap1 and enters the cell nucleus, which transactivates a large number of antioxidants, including HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…OTU deubiquitinase 5 (OTUD5), a protein that interacts with GPX4, can promote ferroptosis resistance during ischemia/reperfusion injury by stabilizing GPX4 expression; in turn, hypoxia/ischemia-induced OTUD5 autophagy can destabilize GPX4, leading to ferroptosis-dependent kidney injury ( 96 ). Vitexin has been found to increase GPX4 expression by activating the NRF2/HO-1 pathway, inhibit the ferroptosis of renal tubule epithelial cells, and significantly reduce renal tubule injury, interstitial fibrosis, and renal inflammation in mice with unilateral ureteral obstruction ( 97 ).…”
Section: The Various Forms Of Cell Death and Urolithiasismentioning
confidence: 99%
“…Recently, it has been found that repressor element 1-silencing transcription factor (REST) is upregulated in renal tubular epithelial cells of AKI patients and mice and leads to renal injury through the regulation of ferroptosis, and that tubular-specific knockdown of REST significantly attenuates the transition from AKI to CKD and ameliorates renal fibrosis [ 311 ]. Treatment with ferroptosis inducers, such as erastin, decreases GPX 4 activity and enhances intracellular lipid peroxidation to aggravate renal fibrosis [ 312 ]. Pretreatment with ferroptosis inhibitors stopped the progression of renal fibrosis by preventing ferroptosis-related lipid peroxidation and GSH depletion.…”
Section: The Crosstalk Of Abnormal Iron Metabolism and Oxidative Stre...mentioning
confidence: 99%
“…Pretreatment with ferroptosis inhibitors stopped the progression of renal fibrosis by preventing ferroptosis-related lipid peroxidation and GSH depletion. In addition, vitexin attenuates CKD by inhibiting ferroptosis in renal tubular epithelial cells through activation of Nrf2 [ 312 ], and formononetin and tectorigenin attenuate renal fibrosis by inhibiting Smad3 [ 313 , 314 ].…”
Section: The Crosstalk Of Abnormal Iron Metabolism and Oxidative Stre...mentioning
confidence: 99%